2020
DOI: 10.1016/j.wneu.2020.06.176
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the Volume of Neurosurgical Care During the Coronavirus Disease 2019 Pandemic

Abstract: Significant reductions occurred in neurosurgical operations, clinic visits, and inpatient consultations during COVID-19. Telehealth was increasingly used for assessments. The long-term effects of the reduced neurosurgical volume and increased telehealth usage on patient outcomes should be explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 20 publications
3
42
0
Order By: Relevance
“…Although the COVID period included in this study was longer than the pre-COVID period by 41 days, there was a notable decline of 52.16% in presentations to the outpatient urology clinics in 12 different centers. In line with this finding, a study conducted during the COVID-19 pandemic period showed a 47% decline in presentation to the outpatient neurosurgical clinics and another study found a decline of approximately 56% in presentation to the outpatient orthopedic clinics during COVID-19 pandemic period [8,9]. In a survey with 60 urologists, approximately 96% of the respondents reported a decline in presentation to the outpatient clinics during the COVID-19 pandemic period at varying degrees [10].…”
Section: Discussionmentioning
confidence: 71%
“…Although the COVID period included in this study was longer than the pre-COVID period by 41 days, there was a notable decline of 52.16% in presentations to the outpatient urology clinics in 12 different centers. In line with this finding, a study conducted during the COVID-19 pandemic period showed a 47% decline in presentation to the outpatient neurosurgical clinics and another study found a decline of approximately 56% in presentation to the outpatient orthopedic clinics during COVID-19 pandemic period [8,9]. In a survey with 60 urologists, approximately 96% of the respondents reported a decline in presentation to the outpatient clinics during the COVID-19 pandemic period at varying degrees [10].…”
Section: Discussionmentioning
confidence: 71%
“…The impact of patient volumes related to COVID-19 across the United States and abroad has been tremendous and continues to evolve. This impact extends beyond any single specialty and has not been limited to the specialty of chronic pain [ 13 , 14 ]. During the height of the pandemic, some ambulatory pain clinics were either completely shut down or severely limited in outpatient services.…”
Section: Impact Of Covid On Apcsmentioning
confidence: 99%
“…To avoid delays of necessary treatment in the future, we advocate adequate education of the public and digitalization of medical consultations. We, as well as other authors [ 4 , 20 , 21 ], suppose that such interventions may help oncological and neurosurgical patients in making an informed decision during the pandemic.…”
Section: Discussionmentioning
confidence: 99%